Karakteristik Mikrobiologi (Total Bakteri, Total Yeast) dan pH Produk Susu Kurma Selama Penyimpanan Suhu Rendah (4-6°C) - Adine, Ailsa Aqilah; Wulandari, Eka; Utama, Dicky Tri (Unpad Press, 2023)
Micro, Small, and Medium Enterprises (MSMEs) make the product date milk to increase milk consumption. However, the maximum storage period of the date milk product cannot be known. This study aimed to determine the effect of storage time for date milk products on microbiological characteristics (total bacteria, total yeast) and pH at low temperatures (4-6℃). This research was conducted using an experimental method using a completely randomized design (CRD) with 4 treatments based on storage time consisting of the 5th day of storage, 10th day of storage, 15th day of storage and 20th day of storage. The research data were analyzed using variance followed by an orthogonal polynomial test. The results showed that the storage time of the product dates milk at low temperature (4-6℃) for 20 days showed a different total bacteria by following the cubic regression pattern in the equation y = 0.165x3 - 1.525x2 + 4.328x + 2.524; different yeast totals with a cubic regression pattern in the equation y = 0.1826x3 - 1.6219x2 + 4.7425x + 1.6895; and a different pH by following the cubic regression pattern in the equation y = -0.044x3 + 0.368x2 - 1.0303x + 7.376. The maximum product storage time up to the 5th day of storage at low temperatures (4-6℃).